'Routine' versus 'Smart Phone Application Based – Intense' follow up of patients with acute coronary syndrome undergoing percutaneous coronary intervention: Impact on clinical outcomes and patient satisfaction. (August 2021) - Yadav, Satyavir; Sethi, Rishi; Pradhan, Akshyaya; Vishwakarma, Pravesh; Bhandari, Monika; Gattani, Raghav; Chandra, Sharad; Chaudhary, Gaurav; Sharma, Akhil; Dwivedi, S.K.; Narain, V.S.; Rao, Bhawna; et al.
Highlights: Smart phone application use in follow up of post intervention acute coronary syndrome patients. This could individualize each patients follow up and shown higher satisfaction and comparable clinical outcomes. This should be explored further for long term benefits. Abstract: Background: Acute coronary syndrome (ACS) refers to the spectrum of clinical presentation of coronary artery disease (CAD). As a routine practice at our institute, following PCI, ACS patients are called for the first follow up after two weeks. This period of two weeks can be full of anxieties, concerns and medical issues. In this study, we planned to assess the feasibility/acceptability of smart phone application (app) based system for patient follow-up and its comparison to routine practice among patients with ACS who have undergone a PCI. Methods: A randomized controlled trial (RCT) was conducted over a period of one year from January to December 2017. After the PCI was deemed successful, patients were recruited and enrolled based on the understanding of basic English language and operation of a smart phone. Those who consented to be part of study were then randomly allocated either the conventional follow up group or the intense follow up (routine + smart phone app based follow up) group. First co- primary outcome was composite of clinical outcomes (mortality, myocardial infarction, stroke, target vessel revascularisation, heart failure admission and emergency visit). Second co- primary outcome was patient satisfaction. The overall patient satisfaction was assessed by the patients using a five-point patient satisfaction survey instrument containing five questions with 5 marks each, in which higher scores meant more satisfaction. Secondary outcome was controlled hypertension in hypertensive patients. It was defined as systolic BP less than 130 and diastolic BP less than 80 mmHg. Results: A cohort of 228 patients (109 in intense app-based arm; 119 in routine follow up arm) were analyzed. The result showed significant improvement in blood pressure control in hypertensive population in intense app based follow up group (76.2%) when compared to routine follow up group (45%) with p value 0.0062. The satisfaction score was significantly higher in the intense app based follow up (20.7 ± 1.29) as compared to routine follow up (16.5 ± 2.68); p value 0.0001. In the intense app based follow up 72.5% patient felt it was excellent tool (score 21–25) while 27.5% categorized it as good (score 16–20). While the routine follows up was perceived as good by most (91.6%) of the patients. Only 4.2% graded it as excellent and an equal number (4.2%) graded it as a poor way of follow up. Conclusions: App based system shows higher satisfaction rate and comparable clinical outcome when compared to traditional hospital based follow up protocol alone. It has a high acceptance rate and thus this system should be explored further to optimize long term patient care.